Proton nuclear magnetic resonance assignments and surface accessibility of Tryptophan residues in lysozyme using photochemically induced dynamic nuclear polarization spectroscopy. - Hore, P; Kaptein, R (1983)
Tryptophan resonances in the 360-MHz 1H photochemically induced dynamic nuclear polarization spectrum of hen egg white lysozyme are investigated in detail. All resonances of one tryptophan and six of another are identified and assigned to their respective protons. The methods employed, all involving nuclear spin polarization, include the study of cross-relaxation effects and the use of selective radio-frequency irradiation, Gd3+ as a paramagnetic probe, and riboflavin as the chemically induced dynamic nuclear polarization generating dye. From a comparison of the experimental results with the known X-ray structure of lysozyme, second-stage assignments of the two tryptophan residues (Trp-62 and Trp-123) are proposed. A number of other resonances are characterized, among them Trp-63 C(2)H and four indirectly polarized methyl groups.